Adjusting to Transitory Shocks: Worker Impact, Firm Channels, and (Lack of) Income Support - Ana Margarida Fernandes; Joana Silva (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper estimates worker and firm impacts of foreign shocks, and the income support provided by assistance programs. It exploits quasi-experimental variation in firms' foreign demand resulting from the global financial crisis, using employer-employee data for Brazil in 2004-2017, linked with firm customs and financial data, and administrative data covering the universe of cash transfer, unemployment insurance, and training beneficiaries. Negative employment effects take over a decade to dissipate fully, wage effects persist, and firm restructuring involves occupational adjustment, increasing permanently skilled workers while reducing unskilled workers. Brazilian workers suffer smaller employment losses in highly informal locations and concentrated sectors. Underlying labor scarring is firm scarring caused by selection (exit) and (revenue, employment and productivity) downsizing. Unemployment insurance and cash transfers yield limited wage loss replacement (6 percent). Training does not increase. The evidence shows that a temporary shock induces persistent effects: firm restructuring scars incumbent workers and increases long-run inequality. Firm scarring may be even more severe in less flexible labor markets. Using data from Ecuador, analysis finds that firms do not adjust workforce composition, but they permanently reduce capital which increases scarring.
Keywords: F14; F16; J24; J46; L25; 330; employment; wages; firms; exports; foreign shocks; global financial crisis